Effectiveness of exercise and health education interventions in Brazilian primary health care - Maria Clara Elias Polo; Giselle Helena Tavares; Ana Carolina Kanitz; Emerson Sebastião; Camila Bosquiero Papini; Danilo Rodrigues Pereira da Silva (Motriz: Revista de Educacao Fisica, 2020)
Abstract AIM This study examined the effectiveness of two different behavioral change interventions to improve Physical Activity (PA) and to reduce Sedentary Behavior (SB) in a primary health care setting. METHODS This quasi-experimental study recruited and enrolled 31 users of a primary health care unit of the Brazilian Unified Health System aged 18 or more. Participants were allocated into two groups: Physical Exercise Group combined with Health Education (EHE) and Health Education Group (HE). The EHE group participated in 60 minutes of exercise, twice a week, and 20 minutes of counseling. The HE group participated in 40 minutes of counseling, once a week. Both programs were conducted for over 18 weeks. PA levels were self-reported (IPAQ) and PA and SB were objectively (accelerometer) assessed before and after the intervention period. Data were analyzed using intention-to-treat analysis with generalized estimating equations adopting p<0.05 for significance. Also, the individual PA and SB deltas were computed. Improvements in PA and SB were observed for both interventions (p<0.05). RESULTS Both groups increased the minutes of weekly leisure PA (p=0.006), time spent in light (p=0.003), and moderated-to-vigorous (p=0.042) PA and decreased the amount of SB, with a significant decrease in the HE group (p=0.010). Delta analyses further demonstrated the effectiveness of the interventions to increase PA in other domains (i.e., transportation, household) and maintenance of occupational PA. CONCLUSION Behavioral change interventions in the primary health care context involving exercise and counseling seem to be effective in improving PA and SB in adults.